Dwight N. Blumer letter to Thomas H. Kent regarding winter bird sightings, January 30, 1983 - Blumer, Dwight N.et al (1983)
Letter from Dwight N. Blumer to Thomas H. Kent regarding winter bird sightings, January 30, 1983. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed/flatbed